Analisis Efisiensi Pemasaran Kakao di Kecamatan Luyo Kabupaten Polewali Mandar - Muhammad Rasyidin; Irmawati Irmawati (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
In Luyo District, cocoa is one of the primary agricultural products, as it significantly contributes to regional income. However, not all existing marketing channels can provide optimal benefits for farmers. Therefore, the primary focus of this study is to analyze the structure of marketing channels, marketing margins, farmers' share, and marketing efficiency levels. The research was conducted from July to September 2023 in Luyo Subdistrict, Polewali Mandar Regency. This location was deliberately chosen because it is part of the Polewali Mandar Regency, which is a major producer of cocoa beans. For farmer sampling, simple random sampling was employed using the Slovin formula, while snowball sampling was used to identify marketing institutions. The total number of respondents was 108, consisting of 97 farmers and 11 marketing institutions. Data collection was conducted through structured interviews using a prepared questionnaire. The analysis method employed was quantitative descriptive analysis, which involved calculating margins, farmers' shares, and marketing efficiency. The research findings concluded that there are six primary channels used by farmers, with the most efficient channel being the sixth channel, as it has the lowest margin value of Rp. 2.000/kg, a high farmer's share of 96.36%, and the lowest efficiency value of 0.89%. These findings indicate that the shorter the distribution channel, the greater the profits earned by farmers as primary producers, and the more efficient the channel. Therefore, it is recommended that farmers collaborate with marketing agencies to increase their income. Additionally, the Polewali Mandar Regency government should support the development of direct marketing models through partnerships with local companies.